Analisis Pengaruh Citra Merek, Persepsi Harga, Sikap Merek, Lokasi dan Word of Mouth Terhadap Niat Menonton di Cinema XXI Kota Padang - Ullya Rahmi Aswin; Danny Hidayat (Management Institute Faculty of Economics Universitas Andalas, 2019)
This study aims to analyze the influence of Brand Image, Price Perception, Brand Attitudes, Location and Word of Mouth to Purchase Intention at Cinema XXI Padang City. The sample of this research is the first time viewers in Cinema XXI in Padang City as many as 208 respondents. The research data processing is done by using SEM (Structural Equation Modeling) method, with the type of Structural Equation Modeling (SEM) used by Smart Pls. The results showed that Brand Image, Price Perception, Brand Attitudes, Location and Word of Mouth positively influence the Purchase Intention